Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Simplify the following expression using Boolean Algebra into sum-of-products (SOP) expressions

. refers to AND + refers to OR

a'.b'.c' + a.b'.c' + a.b.c'

This is what I have so far.

a'.b'.c' + a.b'.c' + a.b.c'

= (b'.c').(a'+a) + a.b.c'

= b'.c' + a.b.c'

Anyway to simplify it further?

share|cite|improve this question
up vote 2 down vote accepted

You can not use associativity when operators are mixed:

$$a'.b'.c' + a.b'.c' + a.b.c' \neq (b'.c').(a'+ a) + a.b.c'\tag{1}$$

It is true that $a'.b'.c' = b'.c'.a'$, by commutativity of ".", but it is not legitimate/not valid to impose parentheses to group $(a' + a)$ as you did.

You can use the distributive laws, and you might want to use Demorgan's Laws, as well.

Example: for using the distributive law, and the fact that $b' + b = 1$ $$a.b'.c' + a.b.c' = a.c'.b' + a.c'.b = a.c'(b'+b) = a.c'$$

Now we've simplified our expression to

$$a'.b'.c' + a.c'\tag{2}$$

There's a common term of $c'$ in each of these products, so we can simplify further. See what you come up with, and I'll work with you to clarify/confirm, etc. if you have any more questions.

$$a'.b'.c' + a.c'=(a'.b' + a).c' $$ $$= [(a'+a).(b'+a)].c' $$ $$= (b'+a).c' = b'.c' + a.c' $$ $$= a.c' + b'.c'$$

share|cite|improve this answer
I see. Then how do I approach the question above? – Lawrence Wong Feb 3 '13 at 16:17
Do you know how the distributive laws work? Do you know DeMorgan's? – amWhy Feb 3 '13 at 16:19
distributive rule x.(y+z) = (x.y) + (x.z) I know DeMorgan rule. – Lawrence Wong Feb 3 '13 at 16:21
a.b′.c′+a.b.c′=a.(b′.c′+b.c′) is not equal to a.b′.c′+a.b.c′=a.c'(b′+b) ? – Lawrence Wong Feb 3 '13 at 16:25
I am really lost. Do you mind guiding me through this question? – Lawrence Wong Feb 3 '13 at 16:32

Please follow @amWhy's approach. Once you get it, you may try to understand this:

$$a'.b'.c' + a.b'.c' + a.b.c'$$ $$=a'.b'.c' + a.b'.c'\mathbf{+ a.b'.c'}+ a.b.c'$$ $$=b'.c'(a'+a)+a.c'(b+b')$$ $$=b'c'+a.c'$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.